Associação da depressão e distúrbio do sono em pacientes com e sem disfunção temporomandibular - Sousa, Luisa Maria Bezerra de (2015)
Objective: To evaluate the inter-relationship between TMD (temporomandibular disorder), depression and sleep disorder. Methods: This is a case-control study with questionnaires in 111 patients, allocated from the Dentistry Department of UFRN, Natal, Brazil, from September 2014 to June 2015, for evaluation of depressive symptoms through the BDI (Beck Depression Inventory); sleep disorder, the PSQI (Pittsburgh Sleep Quality Index) and DTM through the RDC / TMD (diagnostic criteria to search for DTM). All indexes were applied by a single examiner previously trained and calibrated. The collected data were analyzed with chi-square tests of Pearson (χ2) and the unconditional logistic regression. Results: women had a risk of 2.85 times more likely to develop TMD (p = 0.046). The OR (odds ratio) shows that sleep disturbance increases by 2.19 the chances of having TMD (p = 0.062) and depressive symptoms increase the risk by 3.16 times in developing dysfunction (p = 0.053). Conclusion: The data of this research allows us to conclude that patients with TMD, in this population, were more likely to develop changes in sleep and depressive symptoms.